A presença de mercúrio em casa constitui um risco de contaminação humana e / ou ambiental? Relato de um caso Is the presence of mercury at home a risk of human and / or environmental contamination? A case report - Josino C. Moreira; Fatima R. Pivetta; Gisele S. Kuriyama; Paulo R. Barrocas; Fernando L. G. Nicola; Fernanda C. G. Rosa; Silvana C. Jacob (Química Nova, 1997)
Mercury kept in a garage of a residencial building in Rio de Janeiro was accidentally released and caused local (environmental and human) contamination. The concentration of mercury in indoor air of the most critical site reached 15.5 mg/m³. Outdoor air samples showed concentrations ranging from 0.37 to 6.6 mg/m³ . Seventy five per cent of the urine samples collected from 22 residents in the contaminated building showed levels of mercury higher than those observed in non exposed individuals (>6.9 mg/L); in 30% of these samples, the concentration was higher than 20 mg/L. These values show a high level of human contamination and the final consequences were not so serious owing to the quick action taken by one of the residents.